A arte de enfermeiro: Escola de Enfermagem Dr. Ângelo da Fonseca - Ana Isabel Silva (Ciências e Culturas, 2008)
This work analyses the historical development of the Ângelo da Fonseca Nursing School from its foundation tol the present day (1881-2004). It was founded in 1881 by Costa Simões, administrator of the University of Coimbra Hospitals, to provided training for the hospitals' nursing staff. However, this initiative did not last very long, and the School did not begin functioning again until 1919. In 1931, it was renamed in honour of Ângelo da Fonseca, director of the Hospitals. Then, in the 1950s, under the direction of João Porto, it underwent great development, which continued into the following decades, despite the lack of facilities (which only improved in 1978) and the convulsions of the revolutionary period (1974-1976).